Respostas

2014-08-14T16:19:48-03:00
Soma:
A)(2x+1)²=
(2x+1).(2x+1) = 
4x²+2x+2x+1 = 
4x²+4x+1


B)(3y+3a)² =
(3y+3a).(3y+3a) = 
9y²+9ya+9ya+9a² = 
9y²+18ya+9a²


C)(3+x)² =
(3+x).(3+x) = 
9+3x+3x+x² = 
9+6x+x² ou x²+6x+9

 
D)(2x+3y)² =
(2x+3y).(2x+3y) = 
4x²+6xy+6xy+9y² = 
4x²+12xy+9y²

Subtração:
A)(2y-4)² =
(2y-4).(2y-4) =
4y²-8y-8y+16 =
4y²-16y+16


B)(x-2)² =
(x-2).(x-2) = 
x²-2x-2x+4 = 
x²-4x+4


C)(3x-2y)² =
(3x-2y).(3x-2y) = 
9x²-6xy-6xy+4y² =
9x²-12xy+4y²


D)(2n-1)² =
(2n-1).(2n-1) = 
4n²-2n-2n+1
4n²-4n+1

1 1 1